1999
DOI: 10.1063/1.369983
|View full text |Cite
|
Sign up to set email alerts
|

Polarized neutron diffraction study of the extended honeycomb molecular network d20−P(C6D5)4MnFe(C2O4)3

Abstract: Magnetic field driven transition from an antiferromagnetic ground state to a ferrimagnetic state in Rb0.19Ba0.3Mn1.1[Fe(CN)6]·0.48H2O Prussian blue analogue J. Appl. Phys. 112, 093903 (2012); 10.1063/1.4759361Huge influence of hydrogenation on the magnetic properties and structures of the ternary silicide NdMnSiHigh temperature neutron diffraction studies of 0.9 BiFeO 3 -0.1 PbTiO 3The M II and M III magnetic ions in the extended molecular network P͑C 6 D 5 ͒ 4 MnFe͑C 2 O 4 ͒ 3 form a two-dimensional honeycomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…Heat capacity anomaly due to the short range ordering above the magnetic transition temperature in the present case can be well represented by S ¼ 5=2 two-dimensional antiferromagnetic Heisenberg model (H=-2J P S i Á S j ) for a honeycomb lattice with J/k B =À3.3 K. This value is very close to J/k B =À3.9(1) K [11] magnetic heat capacities and the theoretical magnetic heat capacities above T N are in good agreement in the present case. However, as far as the relevant theory is concerned, a two-dimensional pure Heisenberg system cannot exhibit any phase transition due to spin ordering [24].…”
Section: Magnetic Interactionsmentioning
confidence: 56%
See 4 more Smart Citations
“…Heat capacity anomaly due to the short range ordering above the magnetic transition temperature in the present case can be well represented by S ¼ 5=2 two-dimensional antiferromagnetic Heisenberg model (H=-2J P S i Á S j ) for a honeycomb lattice with J/k B =À3.3 K. This value is very close to J/k B =À3.9(1) K [11] magnetic heat capacities and the theoretical magnetic heat capacities above T N are in good agreement in the present case. However, as far as the relevant theory is concerned, a two-dimensional pure Heisenberg system cannot exhibit any phase transition due to spin ordering [24].…”
Section: Magnetic Interactionsmentioning
confidence: 56%
“…Below T N , this and analogous materials exhibited a jump in the magnetization arising probably from the uncompensated magnetic moment [4,6]. Vissar et al [11] assumed the similar uncompensated magnetization observed in {P(C 6 D 5 ) 4 [Mn IIFe III (ox) 3 ]} N as the manifestation of weak ferromagnetic alignment of Mn II and Fe III spins at low temperatures. From the single crystal magnetization measurements of {N-(n-C 5 H 11 ) 4 [Mn IIFe III (ox) 3 ]} N , Carling et al [17] observed an uncompensated magnetization below 27 K. Results from M .…”
Section: Application Of Spin-wave Theorymentioning
confidence: 92%
See 3 more Smart Citations